Meningkatkan Keaktifan Belajar Siswa Melalui Model Problem Based Learning (PBL) Pada Pembelajaran Pendidikan Pancasila Siswa Kelas VIII-A Di SMP Negeri 16 Surabaya - Qurrotul Uyun; Pandu Rudy Widyatama; Muhammad Syaifudin; Maya Mustika Kartika Sari (CV. ULIL ALBAB CORP, 2024)
Learning activity is something that needs to be encouraged and improved in students with the aim of achieving success in learning. However, according to the view, the learning activity of class VIII-A students at SMPN 16 Surabaya still needs to be encouraged and improved. The researcher conducted Class Action Research (CAR) as an effort to create learning that is in accordance with the needs of students and meaningful which can increase student activity in Pancasila Education learning through the Problem Based Learning (PBL) model. This research was conducted through a pre-cycle and two cycles with planning, implementation, observation and evaluation and reflection. The results of the study showed that the application of the Problem Based Learning (PBL) model can increase the learning activity of class VII-A students at SMPN 16 Surabaya, indicated by an increase in the percentage of student learning activity. The increase in student learning activity can be seen based on the results of data tabulation processing in the form of a questionnaire related to learning activity which obtained a percentage of 41.94% in the very poor category in the pre-cycle, 60.00% in cycle I in the good category, and 70.30% in cycle II in the good category.